2021
DOI: 10.3390/polym13193440
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight-Dependent Physical and Photovoltaic Properties of Poly(3-alkylthiophene)s with Butyl, Hexyl, and Octyl Side-Chains

Abstract: A series of poly-3-alkylthiophenes (P3ATs) with butyl (P3BT), hexyl (P3HT), and octyl (P3OT) sidechains and well-defined molecular weights (MWs) were synthesized using Grignard metathesis polymerization. The MWs of P3HTs and P3OTs obtained via gel permeation chromatography agreed well with the calculated MWs ranging from approximately 10 to 70 kDa. Differential scanning calorimetry results showed that the crystalline melting temperature increased with increasing MWs and decreasing alkyl side-chain length, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 65 publications
(79 reference statements)
3
13
0
Order By: Relevance
“…All parameters used to calculate the yields are listed in Table S1 in the supplementary Materials part . The polymerization degree increased with increasing alkyl side-chain length, which can be attributed to the better solubility of the copolymers containing longer alkyl chains in the reaction solvent of THF [ 10 ]. With the high yield of monomer conversion, it can be confirmed that the actual ratio of each P3AT block in the triblock copolymers was virtually the same as the feeding molar ratio of the starting monomers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All parameters used to calculate the yields are listed in Table S1 in the supplementary Materials part . The polymerization degree increased with increasing alkyl side-chain length, which can be attributed to the better solubility of the copolymers containing longer alkyl chains in the reaction solvent of THF [ 10 ]. With the high yield of monomer conversion, it can be confirmed that the actual ratio of each P3AT block in the triblock copolymers was virtually the same as the feeding molar ratio of the starting monomers.…”
Section: Resultsmentioning
confidence: 99%
“…The PCE value of approximately 5% was significantly higher than those of poly(3-butylthiophene) (P3BT) and poly(3-octylthiophene) (P3OT) [ 9 ]. This was attributed to the higher charge carrier extraction capability of the P3HT active layer which is blended with a proper fullerene derivative, owing to its preferable molecular morphology after undergoing the annealing process [ 10 , 11 ]. P3BT might be a suitable material for organic photovoltaic (OPV) applications owing to its higher crystallization facility [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was very promising to select particular functional materials in the design of photovoltaic cells to produce high yield. Molecular weight and alkyl side chain length were investigated for a series of poly(3-alkyl-thiophenes) (P3AT) to elucidate their effect on photovoltaics [127]. P3AT with butyl (C 4 H 9 ), hexyl (C 6 H 13 ), and octyl (C 8 H 17 ) groups were synthesized by adjusting Ni(dppp)Cl 2 catalyst.…”
Section: Novel Organic Semiconductors For Photosensingmentioning
confidence: 99%
“…This study was very promising to select particular functional materials in the design of photovoltaic Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 6 December 2021 cells to produce high yield. Molecular weight and alkyl side chain length were investigated for a series of poly(3-alkylthiophenes) (P3AT) to elucidate their effect on photovoltaics[127]. P3AT with butyl (C4H9), hexyl (C6H13), and octyl (C8H17) groups were synthesized by adjusting Ni(dppp)Cl2 catalyst.…”
mentioning
confidence: 99%